007.1 New and traditional notification tools improve partner notification outcomes among msm with syphilis infection in lima, peru. (13th September 2015) - Clark, Jesse; Oldenburg, Catherine; Segura, Eddy; Rios, Jessica; Villaran, Manuel; Salvatierra, Javier; Gonzales, Pedro; Levine, Deb; Sanchez, Jorge; Lama, Javier
Abstract : Background: Patient-initiated partner notification (PN) is a cornerstone of STD control in resource-limited public health systems. We conducted a randomised, controlled trial of two new tools to support PN among MSM: anonymous, internet-based notification systems and patient-delivered partner referral cards. Methods: We screened 1, 625 MSM for syphilis in Lima, Peru between 2012–2014. Enrollment was limited to MSM with symptomatic primary or secondary syphilis (n = 133) and/or latent syphilis diagnosed by RPR/TPPA (n = 406; Seroprevalence: 25.0%). After enumerating all recent partners and providing details of their three most recent partners, 370 participants were randomly assigned to four intervention arms: 1) Standard PN Counselling (Control) [n = 94]; 2) Counselling and Referral to Internet PN (www.inspot.org ) [n = 95]; 3) Counselling and Provision of 5 Partner Referral Cards [n = 97]; or 4) Counselling with both Internet PN and Partner Referral Cards [n = 84]. Self-reported notification of recent sexual partners was assessed by CASI among the 354 participants who returned for 14-day follow-up. Results: The median age of participants enrolled was 27 (IQR: 23–34), with a median of 3 partners (IQR: 1–5) in the past month and a baseline HIV seroprevalence of 64.1%. Participants referred to internet PN (Arms 2 and 4) or provided with printed partner referral cards (Arms 3 and 4) were more likely to have notified ≥1 partners at 14-day follow-up than participants who received only PN counselling (OR: 2.26 [95% CI: 1.33, 3.82] and 1.94 [95% CI: 1.15, 3.27], respectively). The fraction of all recent partners notified was significantly greater in the Internet PN (56.5%, p < 0.001) and Referral Card (50.8%, p = 0.006) arms than the Control arm (35.3%). Conclusions: Internet notification systems and printed partner referral cards provide inexpensive, effective tools to support patient-directed PN, significantly improving notification by Peruvian MSM with syphilis. Additional research is needed to optimise use of different PN technologies in specific partnership contexts.